A Study on Bidding Trend and Performance of Construction Projects: A Case Study of Water Supply Projects in Koshi Province, Nepal - Khadka, Suman; Adhikari, Sundar; Neupane, Uttam; Kafle, Mukesh; Sharma, Mahesh (International Journal on Engineering Technology and Infrastructure Development, 2026)
Public procurement regulations strongly influence construction project outcomes, particularly in the water supply sector of Nepal. To address contractor over-commitment and aggressive low bidding, the Government of Nepal enacted the 11th and 12th amendments to the Public Procurement Regulations (PPR), 2064, limiting each contractor to a maximum of five concurrent projects. This study evaluates the impact of this regulatory change on bidding behavior, competition, and project performance in water supply projects implemented by federal-level offices of the Department of Water Supply and Sewerage Management (DWSSM) within Koshi Province. A dataset of 108 projects (45 before amendment, n = 63 after amendment) was analyzed using quantitative and descriptive statistical methods to compare pre- and post-amendment periods. Key aspects examined include bidder participation, bid price trends relative to engineer’s estimates, project time performance, and contractor market concentration. Results indicate a statistically significant decline in average bidder numbers from 4.49 to 2.78 (38.1% reduction, p < 0.001), while average bid discounts fell from 28.66% to 11.80% (58.84% reduction, p < 0.001), reflecting considerably more realistic pricing. Project time performance improved dramatically, with mean delay for completed projects falling from 488 days to 48 days (90.1% reduction), and the proportion of projects requiring Extension of Time (EoT) declining from 86.7% to 9.5%. The Herfindahl-Hirschman Index (HHI) decreased from 1,850 to 1,240, indicating measurable market deconcentrating, while unique contractor participation increased from 34 to 55 firms. The findings suggest that regulatory interventions can improve project execution without encouraging underbidding, but sustained monitoring is necessary to prevent collusive bid clustering and single-bidder concentration for large contracts.